Brasil, Irã e a paz no Oriente Médio / Brazil, Iran and peace in the Middle East - Biato, Marcel Fortuna (Mural Internacional, 2010)
A visita do Presidente Lula a Teerã, em maio de 2010, foi um marco na história diplomática brasileira. Como resultado de audacioso esforço negociador, foi possível fazer o aparentemente impossível: levar o Irã a retornar à mesa de negociações com a comunidade internacional em torno de seu programa nuclear. O chamado Acordo de Teerã representou um primeiro passo para restaurar o diálogo, afastando a hipótese de um iminente agravamento das tensões na região. O artigo analisa os ganhos e desafios do Acordo. ABSTRACT President Lula’s visit to Tehran in May 2010 was a landmark in Brazilian diplomatic history. As a result of the bold negotiating effort, the seemingly impossible was made possible: to get Iran back to the negotiating table with the international community about its nuclear programme. The Tehran Agreement represented the first step towards a return to dialogue, allaying fears of an imminent heightening of tensions in the region. The article analyses the positives and challenges of the agreement. Palavras-chave: Política externa brasileira, Acordo de Teerã, questão nuclear. Keywords: Brazilian foreign policy, Tehran Agreement, nuclear question. DOI: http://dx.doi.org/10.12957/rmi.2010.5311